Laser cladding Ni-Ti-Cr alloy coatings with different process parameters. Issue 15 (18th November 2019) - Han, Tengfei; Xiao, Meng; Zhang, Ying; Shen, Yifu
ABSTRACT: In this work, the alloy coatings were fabricated from Ni-Ti-Cr powder by laser cladding with different process parameters on Q235 mild steel. The effects of laser cladding process parameters on the microstructure and properties of the coating were studied. The crack resistance of coating is improved by adjusting process parameters and in situ synthesized NiTi. A good metallurgical bonding is formed between the substrate and the coating and no obvious cracks are found. Under the lowest specific energy, the edge of the coating has no bonding with the substrate. The coatings are mainly composed of NiTi, Cr2 Ti, and Cr. With the increase of specific energy, the grain size of the coatings becomes coarser, and the content of Cr2 Ti increases. The microhardness and wear resistance of the coatings increase at first and then decrease. In comparison to the substrate, the microhardness of coatings is enhanced dramatically, and the highest microhardness was achieved under Es = 50.0 J mm −2 . The wear resistance of the coatings is also improved significantly compared to that of the substrate.